Resistance and Assimilation: Transforming Security Roles of China's Largest Muslim Minorities. Issue 2 (2nd April 2016) - Garcia, Zenel
Abstract: China's resurgence as an economic power has brought it increased interconnectivity to international global markets, and with it, increased exposure to transnational crimes. The rise of Islamic fundamentalism and the resulting increase in religious-inspired terrorist attacks have been of particular concern for the Chinese leadership. This paper aims to highlight the processes of resistance and assimilation of China's two largest Muslim minorities, the Hui and Uyghur, in successive Chinese Empires since the eighth century CE and how critical events in the past two decades have affected the way in which the government of the People's Republic of China (PRC) has approached relations with its Muslim minority communities. The purpose is two-fold: to expose these groups' stabilizing and destabilizing influence throughout the 1300 years of Muslim-Chinese coexistence, and to assess the effectiveness of the Chinese Communist Party's Policies towards its Muslim minorities.